Pengembangan Aplikasi Wedding.co berbasis Web (Studi Kasus: Kota Malang) - Beuty Ayu Fambudi; Adam Hendra Brata; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In the era of information technology development as it is now certainly will affect the increasing competitiveness of the business world. Wedding organizer company is one of the companies engaged in the service sector that requires assistance from the advancement of information technology such as websites. Changes in lifestyle and financial capabilities make the bride and groom often do not have enough time in preparing for their wedding. The wedding.co application development is an application that can provide a service for brides who will order a wedding package service in real time. The wedding.co application development acts as a platform to bring together wedding organizer companies in Malang with prospective brides. The application development process uses waterfall method with prototyping model requirements engineering, starts from the requirements engineering phase to the testing phase with an object-oriented approach. At the requirements engineering phase, there are 67 functional requirements and 1 non-functional requirement. The implementation phase of this application is done using the PHP programming language, Laravel framework, and MySQL database. The testing phase conducted is unit testing with 100% valid data from 3 functionality tested, integration testing with 100% valid data from 1 functionality tested, and validation testing with 100% valid data from 32 functionality tested. Non-functional testing is tested using the compatibility parameter conducted proves that this application can run on 6 browsers, namely Internet Explorer, Edge, Mozilla Firefox, Google Chrome, iOS, and Android.